PEMBELAJARAN MENULIS TEKS BIOGRAFI DENGAN MEDIA FILM PADA SISWA SMA MERDEKA SOREANG KELAS X IPA - Kusmayanti, Yanti; Sugihanti, Fitri (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Writing is one of the language skills that students must master. Writing is used as a means to convey information either directly or indirectly. This study aims to determine the significant differences between the ability to write biographical text before the students after treatment of the use of film media; and students' responses to the use of film media in learning to write biographical texts. The research method is experimental method with pretest-posttest one group design design. The sample of research is the students of class X IPA SMK Merdeka Soreang. The result of the research shows that the average score of writing ability of biography of students has increased by the difference of the average value of 23.80. The average grade of the experimental class students on pretest was 61.73 and posttest 84.53. Meanwhile, based on the questionnaire results, it is known that about 79% of students agree with the application of film media in biographical writing, while 21% are still in doubt.